2018
DOI: 10.1101/448365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wolbachia endosymbionts subvert the endoplasmic reticulum to acquire host membranes without triggering ER stress

Abstract: The reproductive parasite Wolbachia are the most common endosymbionts on earth, present in a plethora of arthropod species. They have been introduced into mosquitos to successfully prevent the spread of vector-borne diseases, yet the strategies of host cell subversion underlying their obligate intracellular lifestyle remain to be explored in depth in order to gain insights into the mechanisms of pathogen-blocking. Like some other intracellular bacteria, Wolbachia reside in a host-derived vacuole in order to re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…One of the most strongly associated SNPs is found in a gene associated with the endoplasmic reticulum (ER) membrane (XBP1) [69]. Consistent with this functional prediction, a recent study on a wMel-infected D. melanogaster cell line found that Wolbachia resides within ER-derived membrane near and within the ER itself [70]. Modifying this membrane might therefore enable the host to impact Wolbachia titer on the cellular level.…”
Section: Host Genotypes Associated With Wolbachia Titermentioning
confidence: 73%
“…One of the most strongly associated SNPs is found in a gene associated with the endoplasmic reticulum (ER) membrane (XBP1) [69]. Consistent with this functional prediction, a recent study on a wMel-infected D. melanogaster cell line found that Wolbachia resides within ER-derived membrane near and within the ER itself [70]. Modifying this membrane might therefore enable the host to impact Wolbachia titer on the cellular level.…”
Section: Host Genotypes Associated With Wolbachia Titermentioning
confidence: 73%
“…Wolbachia and its host have a long history of co-evolution, and the interaction between both parters is very complex, which has not been clearly clari ed so far [30]. Wolbachia is mainly located in the insect host reproductive system [26], including female ovary and male testis which makes them good materials for studying Wolbachia-host interaction. Previous results based on the transcriptomic data of the testis tissue of the third instar larvae of Drosophila have shown that Wolbachia infection can affect the expression of genes related to spermatogenesis and thus may induce CI [27].…”
Section: Discussionmentioning
confidence: 99%
“…Wolbachia is mainly localized in the reproductive tissues of host [26], which is a good material for studying the interaction between Wolbachia and host. Previous studies have showed that Wolbachia affects the early spermatogenesis process [27].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Wolbachia may alter host protein synthesis as well as ubiquitination-mediated proteolysis to obtain amino acids as their primary source of nutrition. Consistent with using host protein synthesis and degradation pathways for its own nutrition, Wolbachia induces the reorganization of host cell endoplasmic reticulum (ER) and surrounds itself with ER-derived membrane (Fattouh et al 2019), creating a niche near translation and proteolysis machinery. Given that ubiquitination and protein turnover is involved in host cellular differentiation (Kimata 2019), Wolbachia may have co-opted its nutrition-provisioning genes for host manipulation.…”
Section: B Other Known Strategies Of Wolbachia-mediated Control Of mentioning
confidence: 99%
“…Reciprocal control over host/symbiont processes works through endogenous and mimicked mechanisms (dashed lines). B) An example of how host-symbiont interactions (straight arrows) function with endogenous mechanisms (curved arrows) to cause phenotypic changes in cell state, such as symbiont-induced formation of an intracellular replicative niche derived from the endoplasmic reticulum membrane, as has been reported for Wolbachia (Fattouh et al 2019) and a variety of other symbionts (see text). The theory of bacterial endosymbiont genome evolution posits that upon host restriction, bacterial chromosomes begin degrading due to the accumulation of deleterious mutations and the subsequent deletion of pseudogenized regions.…”
Section: C Exploring Overlooked Mechanisms: Future Prospects In Wolmentioning
confidence: 99%